2016
DOI: 10.1074/jbc.m116.750257
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Anti-inflammatory Activity in Vitro and in Vivo of a Novel Antimicrobial Candidate

Abstract: The synthetic antimicrobial peptide SET-M33 has strong activity against bacterial infections caused by Gram-negative bacteria. It is currently in preclinical development as a new drug to treat lung infections caused by Gram-negative bacteria. Here we report its strong anti-inflammatory activity in terms of reduced expression of a number of cytokines, enzymes, and signal transduction factors involved in inflammation triggered by LPS from Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli. Sixte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…SET-M33 is a novel AMP, active in vitro and in vivo against Gramnegative bacteria and showing an acceptable toxicity profile on human cells and in mice [5,8,10,33,34]. In this work, we have shown that it can be synergistic with a number of antibiotics of different families (including those that can be administered also by aerosol) against representative strains of MDR/XDR Gram-negative pathogens.…”
Section: Discussionmentioning
confidence: 95%
“…SET-M33 is a novel AMP, active in vitro and in vivo against Gramnegative bacteria and showing an acceptable toxicity profile on human cells and in mice [5,8,10,33,34]. In this work, we have shown that it can be synergistic with a number of antibiotics of different families (including those that can be administered also by aerosol) against representative strains of MDR/XDR Gram-negative pathogens.…”
Section: Discussionmentioning
confidence: 95%
“…Synthesizing AMP polymers using dendrimer or other AMP nanoparticles to increase the local concentration of the AMP can lower the required dose and combat multidrug-resistant bacteria [133][134][135][136]. (iii) The development of in vitro tests and computational predictions, for example, testing for similarities with allergens, can help to evaluate the immunogenicity and allergenic potential of newly developed AMPs [137], e.g., the basophil activation test [138], cytokine assays [139], lymphocyte activation analysis [140], and Structural Database of Allergenic Proteins (SDAP) [141][142][143]. Although these tools cannot fully predict the allergenic effects of a new AMP in the clinic, they provide a promising preclinical tools for evaluating peptide-based drugs.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…7 Like other antimicrobial peptides, 14 SET-M33 also features anti-inflammatory activity. 8 A study dealing with the antimicrobial mechanism of action of SET-M33 demonstrated that after an initial binding to the bacterial cell wall lipopolysaccharide, the peptide interacts with the bacterial membrane and acquires an amphipathic helix structure. This structure may be partially embedded into the membrane, thereby destroying its function and eventually the cell itself.…”
Section: Introductionmentioning
confidence: 99%